Finding of principle square root of a real number by using interpolation method - Regmi, Rajendra Prasad (Janapriya Journal of Interdisciplinary Studies, 2018)
There are various methods of finding the square roots of positive real number. This paper deals with finding the principle square root of positive real numbers by using Lagrange’s and Newton’s interpolation method. The interpolation method is the process of finding the values of unknown quantity (y) between two known quantities.